BALDONE SCHMIDT (LATVIA) TELESCOPE ASTROPHOTOS ARCHIVE - Eglite, M.; Eglitis, I. (Одеські астрономічні публікації, 2016)
From 1967 to 2005, many astrophotos have been taken with the Baldone Schmidt telescope (80cmx120cmx240cm). These photos have being archived in theInstituteofAstronomyof theUniversityofLatvia(IAU code 069, longitude 24.4041 E, latitude 56.7734 N, altitude103 m). There are over 22000 direct and 2300 spectral photos of different regions of the sky in this archive. There are also information on the photo materials type as well as the types of color filters used for phographiing the sky fields and objects. The home page of theInstituteofAstronomy’s Baldone observatory (www.baldoneobservatory.lu.lv) has the archive’s description. Part of the description has also being published (Alksnis, et al., 1998).